Zirconia ceramic slurry, preparation method thereof, zirconia ceramic product and production method thereof
By adding linear polymer and thermal initiator to the zirconia ceramic slurry and performing drying treatment, the problem of low density and mechanical properties of zirconia ceramic products is solved, and efficient manufacturing of ceramic precision components is achieved.
Patent Information
- Application Number
- CN202411519544.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-07
AI Technical Summary
The slurry of existing photocured zirconia ceramic products has problems such as low solid content, poor fluidity, and uneven dispersion, resulting in low density and poor mechanical properties of 3D printing products, limiting their application in ceramic precision components.
Add linear polymer and thermal initiator to the zirconia ceramic slurry and dry after 3D printing. The linear polymer is polymerized and cross-linked. The thermal initiator causes thermal polymerization to improve the induction of the primitive and final firing. Density and mechanical properties, while improving powder dispersion and bulk density through modified zirconia powder and particle size grading.
It significantly improves the density and mechanical properties of zirconia ceramic products, and enhances its application potential in ceramic precision components.
Smart Images

Figure CN119263823A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of 3D printing materials, and in particular to a zirconia ceramic slurry and a preparation method thereof, a zirconia ceramic product and a production method thereof. Background Art
[0002] Ceramic 3D printing, as a rapid prototyping and small-batch personalized customization manufacturing technology in additive manufacturing, is receiving more and more attention. Ceramic photocuring technology, as an emerging technology in 3D printing, has a fast molding process, no thermal stress, simple equipment, and extremely high raw material utilization. Applying 3D printing technology to the manufacture of ceramics can effectively overcome the shortcomings of traditional ceramic manufacturing technology and can produce ceramic parts with complex shapes, high precision and low cost.
[0003] Zirconia, as an oxide ceramic material with special transformation characteristics, has been widely used in structural materials, biomedical materials, wear-resistant materials and other fields due to its excellent chemical stability and antioxidant ability, excellent flexural strength, wear resistance and biocompatibility.
[0004] However, the slurry used in the current photocuring zirconia ceramic products has problems such as low solid content, poor fluidity, and uneven dispersion. In addition, the 3D printed zirconia products have lower density than zirconia prepared by traditional processes, and the poor mechanical properties also restrict their application in ceramic precision parts. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a zirconia ceramic slurry and a preparation method thereof, a zirconia ceramic product and a production method thereof. The present invention adds a linear polymer and a thermal initiator to the zirconia ceramic slurry, and first performs a drying treatment after 3D printing. During the drying process, the linear polymer is polymerized and cross-linked, and the thermal initiator further induces thermal polymerization of the green blank, thereby increasing the density before degreasing and sintering, thereby improving the density and mechanical properties after degreasing and sintering, and has broad application prospects.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a zirconia ceramic slurry, the zirconia ceramic slurry comprising: zirconia powder and a resin component;
[0008] The resin components include a photosensitive resin, a photoinitiator, a linear polymer and a thermal initiator.
[0009] In the present invention, by adding linear polymers and thermal initiators, the green body further undergoes interlayer bonding and thermal polymerization during the drying heat treatment process after printing, forming physical entanglements between ceramic particles and between layers, making the connection between layers more firm and improving the density of the green body; due to the increase in the density of the green body, the final sintered density of the finished product after degreasing and sintering is improved, and the mechanical properties are significantly improved. Furthermore, the linear polymer has the function of a common dispersant, that is, it increases the wetting effect on the surface of the powder, making the zirconium oxide powder easier to disperse in the medium, which is conducive to increasing the amount of zirconium oxide powder added and improving the printing effect.
[0010] Preferably, the zirconium oxide powder is modified zirconium oxide powder.
[0011] In order to further improve the dispersion uniformity and suspension stability of zirconium oxide powder in the resin liquid, the zirconium oxide powder will be surface-modified before being added to the resin liquid to further improve its compatibility and suspension ability with the photosensitive resin.
[0012] Preferably, the modified zirconia powder is a yttria-doped zirconia powder modified by a modifier. Preferably, the content of yttria in the yttria-doped zirconia powder is 5wt% to 6.5wt%, for example, 5wt%, 5.2wt%, 5.4wt%, 5.5wt%, 5.7wt%, 5.9wt%, 6wt%, 6.2wt%, 6.4wt% or 6.5wt%, etc.
[0013] Preferably, the amount of the modifier added is 0.4-1wt% of the mass fraction of the modified zirconia powder, for example, it can be 0.4wt%, 0.47wt%, 0.54wt%, 0.6wt%, 0.67wt%, 0.74wt%, 0.8wt%, 0.87wt%, 0.94wt% or 1wt%, etc., but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0014] Preferably, the modifier comprises any one of methacrylic acid, 3-(methacryloyloxy)propyltrimethoxysilane or stearic acid, or a combination of at least two thereof, wherein typical but non-limiting combinations are a combination of methacrylic acid and 3-(methacryloyloxy)propyltrimethoxysilane, a combination of methacrylic acid and stearic acid, and a combination of stearic acid and 3-(methacryloyloxy)propyltrimethoxysilane.
[0015] Preferably, the preparation of the modified zirconia powder comprises: mixing initial zirconia powder, a modifier and an organic solvent, performing a first ball milling, and then sequentially drying and sieving to obtain the modified zirconia powder.
[0016] Preferably, the organic solvent comprises ethanol.
[0017] Preferably, in terms of mass ratio, the ratio of organic solvent to initial zirconium oxide powder to abrasive in the first ball mill is 1 to 3: 1: 2 to 5, and the number of organic solvents can be, for example, 1, 1.3, 1.5, 1.7, 1.9, 2.2, 2.4, 2.6, 2.8 or 3, etc.; the number of abrasives can be, for example, 2, 2.4, 2.7, 3, 3.4, 3.7, 4, 4.4, 4.7 or 5, etc., but are not limited to the listed values, and other values not listed within the range are also applicable.
[0018] Preferably, the abrasive material comprises grinding balls of at least two sizes.
[0019] Preferably, the sieving is through a 100 mesh sieve.
[0020] Preferably, the rotation speed of the first ball mill is 500-1000 r / min, for example, it can be 500 r / min, 550 r / min, 610 r / min, 660 r / min, 720 r / min, 770 r / min, 830 r / min, 880 r / min, 940 r / min or 1000 r / min, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0021] Preferably, the first ball milling time is 4 to 6 h, for example, 4 h, 4.3 h, 4.5 h, 4.7 h, 4.9 h, 5.2 h, 5.4 h, 5.6 h, 5.8 h or 6 h, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0022] Preferably, the initial zirconia powder comprises zirconia of a first particle size, zirconia of a second particle size and zirconia of a third particle size, wherein the particle size of the first particle size zirconia is larger than that of the second particle size zirconia, and the particle size of the second particle size zirconia is larger than that of the third particle size zirconia.
[0023] Preferably, the particle size range of the first particle size zirconium oxide is 800-1300 nm, for example, it can be 800 nm, 850 nm, 910 nm, 960 nm, 1020 nm, 1070 nm, 1130 nm, 1180 nm, 1245 nm or 1300 nm, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0024] Preferably, the particle size range of the second particle size zirconium oxide is 200-500 nm, for example, it can be 200 nm, 234 nm, 267 nm, 300 nm, 334 nm, 367 nm, 400 nm, 434 nm, 467 nm or 500 nm, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0025] Preferably, the particle size range of the third particle size zirconium oxide is 50-150 nm, for example, it can be 50 nm, 62 nm, 73 nm, 84 nm, 95 nm, 106 nm, 117 nm, 128 nm, 139 nm or 150 nm, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0026] Preferably, the mass fraction of the first particle size zirconium oxide in the total zirconium oxide powder is 50-70%, for example, it can be 50%, 53%, 55%, 57%, 59%, 62%, 64%, 66%, 68% or 70%, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0027] Preferably, the mass fraction of the second particle size zirconium oxide in the total zirconium oxide powder is 15-40%, for example, it can be 15%, 18%, 21%, 24%, 27%, 29%, 32%, 35%, 38% or 40%, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0028] Preferably, the mass fraction of the third particle size zirconium oxide in the total zirconium oxide powder is 0.1-15%, for example, it can be 0.1%, 1.8%, 3.5%, 5.1%, 6.8%, 8.4%, 10.1%, 11.7%, 13.4% or 15%, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0029] The zirconia slurry used for 3D printing is composed of two major parts: a resin component and zirconia ceramic powder. The volume or mass fraction of the zirconia ceramic powder as a percentage of the total slurry is called the solid content. The higher the solid content, the easier it is to achieve the density and mechanical properties of the final ceramic product. In order to maximize the solid content while effectively controlling the viscosity, spherical powders of different particle sizes are used for stacking. Appropriate particle size and proportion distribution can achieve a higher stacking density, which makes it easier to achieve an increase in the density of the final product. The present invention increases the stacking density of the powder in the slurry, increases the solid content of the zirconia slurry, and ultimately increases the density of the zirconia ceramic blank by performing the above-mentioned grading on the zirconia powder.
[0030] Preferably, the zirconia ceramic slurry comprises: 80-83wt% zirconia powder and 17-20wt% resin component. The 80-83wt% zirconia powder may be, for example, 80wt%, 80.4wt%, 80.7wt%, 81wt%, 81.4wt%, 81.7wt%, 82wt%, 82.4wt%, 82.7wt% or 83wt%, etc., but is not limited to the listed values, and other values not listed in the range are also applicable; the 17-20wt% resin component may be, for example, 17wt%, 17.4wt%, 17.7wt%, 18wt%, 18.4wt%, 18.7wt%, 19wt%, 19.4wt%, 19.7wt% or 20wt%, etc., but is not limited to the listed values, and other values not listed in the range are also applicable.
[0031] Preferably, based on the zirconia ceramic slurry, the content of the photosensitive resin is 6 to 14.8 wt%, for example, it can be 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt% or 14.8 wt%, etc., but is not limited to the listed values, and other values not listed within the range are also applicable.
[0032] Preferably, based on the zirconia ceramic slurry, the content of the photoinitiator is 2 to 4wt%, for example, it can be 2wt%, 2.3wt%, 2.5wt%, 2.7wt%, 2.9wt%, 3.2wt%, 3.4wt%, 3.6wt%, 3.8wt% or 4wt%, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0033] Preferably, based on the zirconia ceramic slurry, the content of the thermal initiator is 0.1 to 1 wt%, for example, it can be 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt% or 1 wt%, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable, preferably 0.1 to 0.3 wt%.
[0034] Preferably, based on the zirconia ceramic slurry, the content of the linear polymer is 2 to 4 wt%, for example, it can be 2wt%, 2.3wt%, 2.5wt%, 2.7wt%, 2.9wt%, 3.2wt%, 3.4wt%, 3.6wt%, 3.8wt% or 4wt%, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0035] Preferably, the photosensitive resin comprises, in terms of mass percentage, 2-5% oligomer and 4-9.8% reactive diluent. The oligomer 2-5% may be, for example, 2%, 2.4%, 2.7%, 3%, 3.4%, 3.7%, 4%, 4.4%, 4.7% or 5%, etc., but is not limited to the listed values, and other values not listed in the range are also applicable; the reactive diluent 4-9.8% may be, for example, 4%, 4.7%, 5.4%, 6%, 6.7%, 7.4%, 8%, 8.7%, 9.4% or 9.8%, etc., but is not limited to the listed values, and other values not listed in the range are also applicable.
[0036] Preferably, the weight average molecular weight of the oligomer is 500-100,000.
[0037] Preferably, the oligomer comprises an acrylate oligomer, preferably comprises any one or a combination of at least two of epoxy acrylate, polyester acrylate or polyurethane acrylate, wherein typical but non-limiting combinations are a combination of epoxy acrylate and polyester acrylate, a combination of polyurethane acrylate and polyester acrylate, and a combination of epoxy acrylate and polyurethane acrylate.
[0038] Preferably, the reactive diluent comprises any one or a combination of at least two of hydroxyethyl methacrylate, isooctyl acrylate, cyclic trimethylolpropane formal acrylate, 1,6-hexanediol diacrylate, triethylene glycol diacrylate, pentaerythritol triacrylate, tetrahydrofuran methyl acrylate, ditrimethylolpropane tetraacrylate or polyethylene glycol diacrylate, wherein a typical but non-limiting combination is a combination of hydroxyethyl methacrylate and isooctyl acrylate, a combination of triethylene glycol diacrylate and isooctyl acrylate, a combination of hydroxyethyl methacrylate and ditrimethylolpropane tetraacrylate, and a combination of polyethylene glycol diacrylate and isooctyl acrylate.
[0039] Preferably, the photoinitiator includes any one of 1-hydroxycyclohexyl phenyl ketone, bis (2,6-difluoro-3-pyrrolophenyl) titanocene, phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide, 2-hydroxy-2-methyl-1-phenyl-1-propanone, diphenyl-(2,4,6-trimethylbenzoyl) phosphine oxide, photoinitiator 1300 or camphorquinone, or a combination of at least two thereof, wherein a typical but non-limiting combination is a combination of 1-hydroxycyclohexyl phenyl ketone and bis (2,6-difluoro-3-pyrrolophenyl) titanocene, a combination of 2-hydroxy-2-methyl-1-phenyl-1-propanone and bis (2,6-difluoro-3-pyrrolophenyl) titanocene, a combination of 1-hydroxycyclohexyl phenyl ketone and 2-hydroxy-2-methyl-1-phenyl-1-propanone, and a combination of photoinitiator 1300 and bis (2,6-difluoro-3-pyrrolophenyl) titanocene.
[0040] Preferably, the thermal initiator comprises an organic peroxide initiator, preferably any one of dicumyl peroxide, dibenzoyl peroxide or tert-butyl hydroperoxide, or a combination of at least two thereof, wherein a typical but non-limiting combination is a combination of dicumyl peroxide and dibenzoyl peroxide, a combination of tert-butyl hydroperoxide and dibenzoyl peroxide, and a combination of dicumyl peroxide and tert-butyl hydroperoxide.
[0041] Preferably, the linear polymer comprises any one of polycaprolactone, polyethylene glycol or polyisoboric acid ester or a combination of at least two thereof, wherein typical but non-limiting combinations are a combination of polycaprolactone and polyethylene glycol, a combination of polycaprolactone and polyisoboric acid ester, and a combination of polyethylene glycol and polyisoboric acid ester.
[0042] Preferably, the zirconia ceramic slurry further comprises an additive.
[0043] Preferably, in terms of mass percentage, the additives include 1-2% dispersant and 0.1-0.3% defoamer. The dispersant 1-2% may be, for example, 1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2%, etc., but is not limited to the listed values, and other values not listed in the range are also applicable. The defoamer 0.1-0.3% may be, for example, 0.1%, 0.13%, 0.15%, 0.17%, 0.19%, 0.22%, 0.24%, 0.26%, 0.28% or 0.3%, etc., but is not limited to the listed values, and other values not listed in the range are also applicable.
[0044] The present invention can improve the dispersion uniformity of zirconium oxide powder in the resin system and reduce the viscosity by adding the dispersant and controlling the range, which is more conducive to the printing process.
[0045] Preferably, the dispersant includes any one of stearic acid, oleic acid, polyvinyl pyridone, sodium polyacrylate, polypropoxy quaternary ternary ammonium chloride, ammonium polyacrylate, silane coupling agent, BYK101, BYK103, KOS110, KOS163, Solsperse2000, Digao 685, Shanggao 9030 or Shanggao 9070, or a combination of at least two of them, wherein typical but non-limiting combinations are a combination of polyvinyl pyridone and sodium polyacrylate, a combination of a silane coupling agent and sodium polyacrylate, a combination of polyvinyl pyridone and Solsperse2000, and a combination of Shanggao 9030 and sodium polyacrylate.
[0046] Preferably, the silane coupling agent includes any one of γ-aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane or γ-methacryloxypropyl trimethoxysilane, or a combination of at least two thereof, wherein a typical but non-limiting combination is a combination of γ-aminopropyl triethoxysilane and γ-glycidyloxypropyl trimethoxysilane, a combination of γ-methacryloxypropyl trimethoxysilane and γ-glycidyloxypropyl trimethoxysilane, and a combination of γ-aminopropyl triethoxysilane and γ-methacryloxypropyl trimethoxysilane.
[0047] Preferably, the defoaming agent comprises any one of n-octanol, BYK-1790, BYK-1794, Digo-Airex 920, AKN-39203 or AKN-3386, or a combination of at least two thereof, wherein typical but non-limiting combinations are a combination of n-octanol and BYK-1790, a combination of BYK-1794 and BYK-1790, a combination of Digo-Airex 920 and BYK-1790, a combination of n-octanol and AKN-3386, and a combination of n-octanol and BYK-1790.
[0048] In a second aspect, the present invention provides a method for preparing the zirconia ceramic slurry according to the first aspect, the preparation method comprising:
[0049] First, a photosensitive resin, a photoinitiator and a linear polymer are mixed to obtain a first resin solution.
[0050] The second mixed zirconium oxide powder and the first resin liquid are stirred and second ball-milled in sequence to obtain a first slurry, and a thermal initiator is added and third ball-milled to obtain a second slurry;
[0051] The second slurry is defoamed to obtain the zirconia ceramic slurry.
[0052] The present invention preferably mixes the first resin liquid first, then adds the zirconium oxide powder, and finally adds the thermal initiator, so that the resin components are mixed more evenly and step-by-step mixing is achieved to achieve the purpose of fully mixing the final slurry. If the thermal initiator is added to the first resin liquid at the same time, because the mixing process of the first resin liquid requires water bath heating and the second ball milling time is relatively long, there may be a risk of local overheating during the ball milling process, causing the thermal initiator to induce partial curing of the resin.
[0053] Preferably, additives are also added during the first mixing.
[0054] Preferably, the temperature of the first mixing is 50-70°C, for example, it can be 50°C, 53°C, 55°C, 57°C, 59°C, 62°C, 64°C, 66°C, 68°C or 70°C, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0055] Preferably, the first mixing time is 1 to 2 hours, for example, 1 hour, 1.2 hours, 1.3 hours, 1.4 hours, 1.5 hours, 1.6 hours, 1.7 hours, 1.8 hours, 1.9 hours or 2 hours, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0056] Preferably, the first mixing is performed under ultrasound.
[0057] In order to make the first resin liquid disperse more evenly, the above process is adopted to ensure that each component system in the first resin liquid can be fully dissolved and dispersed.
[0058] Preferably, the stirring time is 1 to 2 h, for example, 1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h or 2 h, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0059] Preferably, the stirring speed is 800 r / min to 1400 r / min, for example, it can be 800 r / min, 867 r / min, 934 r / min, 1000 r / min, 1067 r / min, 1134 r / min, 1200 r / min, 1267 r / min, 1334 r / min or 1400 r / min.
[0060] Preferably, the rotation speed of the second ball mill is 600-900 r / min, for example, it can be 600 r / min, 630 r / min, 660 r / min, 700 r / min, 730 r / min, 760 r / min, 800 r / min, 830 r / min, 860 r / min or 900 r / min, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0061] Preferably, the second ball mill is milled for 0.5 to 1.5 hours, for example, 0.5 hours, 0.7 hours, 0.8 hours, 0.9 hours, 1 hour, 1.1 hours, 1.2 hours, 1.3 hours, 1.4 hours or 1.5 hours, but are not limited to the listed values, and other values not listed within the range are equally applicable. The pause is 5 to 15 minutes, for example, 5 minutes, 7 minutes, 8 minutes, 9 minutes, 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes or 15 minutes, but are not limited to the listed values, and other values not listed within the range are equally applicable.
[0062] Preferably, the second ball milling time is 8 to 16 h, for example, 8 h, 8.9 h, 9.8 h, 10.7 h, 11.6 h, 12.5 h, 13.4 h, 14.3 h, 15.2 h or 16 h, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0063] Preferably, the rotation speed of the third ball mill is 600-900 r / min, for example, it can be 600 r / min, 630 r / min, 660 r / min, 700 r / min, 730 r / min, 760 r / min, 800 r / min, 834 r / min, 867 r / min or 900 r / min, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0064] Preferably, the third ball milling time is 1 to 2 h, for example, 1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h or 2 h, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0065] Preferably, the third ball milling is performed for 15 to 45 minutes, for example, 15 minutes, 19 minutes, 22 minutes, 25 minutes, 29 minutes, 32 minutes, 35 minutes, 39 minutes, 42 minutes or 45 minutes, but not limited to the listed values, and other values not listed within the range are equally applicable. The pause is performed for 2 to 8 minutes, for example, 2 minutes, 2.7 minutes, 3.4 minutes, 4 minutes, 4.7 minutes, 5.4 minutes, 6 minutes, 6.7 minutes, 7.4 minutes or 8 minutes, but not limited to the listed values, and other values not listed within the range are equally applicable.
[0066] Preferably, the vacuum degree of the defoaming treatment is -0.05 to -0.1 MPa, for example, it can be 0.05 MPa, 0.06 MPa, 0.07 MPa, 0.08 MPa, 0.09 MPa or 0.1 MPa, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0067] Preferably, the defoaming time of the defoaming treatment is 2 to 4 hours, for example, it can be 2 hours, 2.3 hours, 2.5 hours, 2.7 hours, 2.9 hours, 3.2 hours, 3.4 hours, 3.6 hours, 3.8 hours or 4 hours, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0068] The defoaming treatment of the present invention is carried out by using a vacuum defoaming machine until no obvious bubbles are generated on the surface of the slurry, and the degassed zirconia ceramic slurry is transferred to a light-shielding bottle for storage in the dark for later use.
[0069] In a third aspect, the present invention provides a method for producing a zirconia ceramic product, the production method comprising:
[0070] The zirconia ceramic slurry described in the first aspect is 3D printed to obtain a first green body.
[0071] The first green body is dried, degreased and sintered in sequence to obtain the zirconia ceramic product.
[0072] The production method of the zirconia ceramic product of the present invention adds a drying process after printing, so that the linear polymer and thermal initiator in the resin component can play a role, improve the density of the green blank, and then reduce the sintering resistance of the product during the final firing process, thereby improving the final firing density and mechanical properties of the final product.
[0073] Those skilled in the art will appreciate that, before printing, the printer is leveled and calibrated, and then the ceramic slurry prepared as described above is placed in a material tank of the 3D printing device, and the printing parameters are set according to the properties of the slurry to complete the printing of the sample.
[0074] Those skilled in the art understand that after printing is completed, a special tool is used to disassemble the printed sample without damaging the printed substrate, and a cleaning fluid or alcohol is used to remove the support and clean it. In order to prevent the residual cleaning fluid from corroding the sample, the residual cleaning fluid needs to be blown away with a spray gun after cleaning to obtain the first blank.
[0075] Preferably, the density of the first blank is ≥3.5 g / cm 3 , for example, it can be 3.5g / cm 3 、3.52g / cm 3 、3.53g / cm 3 、3.54g / cm 3 、3.55g / cm 3 、3.56g / cm 3 、3.57g / cm 3 、3.58g / cm 3 、3.6g / cm 3 、3.62g / cm 3 、3.65g / cm 3 or 3.7 g / cm 3 wait.
[0076] Preferably, the drying temperature is 120-200°C, for example, it can be 120°C, 129°C, 138°C, 147°C, 156°C, 165°C, 174°C, 183°C, 192°C or 200°C, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0077] Preferably, the drying insulation time is 2 to 4 hours, for example, it can be 2 hours, 2.3 hours, 2.5 hours, 2.7 hours, 2.9 hours, 3.2 hours, 3.4 hours, 3.6 hours, 3.8 hours or 4 hours, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0078] The present invention has no special restrictions on the degreasing and sintering in the above process. Any method known to those skilled in the art for degreasing and sintering can be used, and can also be adjusted according to the actual process. For example, the sample can be placed in a degreasing furnace, and a sintering curve can be set for degreasing and sintering. The degreasing sample is transferred to a ceramic sintering furnace and final sintering is performed according to the set curve.
[0079] In a fourth aspect, the present invention provides a zirconia ceramic product, wherein the zirconia ceramic product is produced by the production method of the zirconia ceramic product described in the fourth aspect.
[0080] Preferably, the green body density of the zirconia ceramic product is ≥3.6 g / cm 3 , for example, it can be 3.6 g / cm 3 、3.61g / cm 3 、3.65g / cm 3 、3.7g / cm 3 、3.8g / cm 3 、3.9g / cm 3 , 4.0g / cm 3 , 4.2g / cm 3 , 4.3g / cm 3 4.5g / cm 3 or 4.8g / cm 3 wait.
[0081] Compared with the prior art, the present invention has at least the following beneficial effects:
[0082] The zirconia ceramic slurry provided by the present invention is added with a linear polymer and a thermal initiator, wherein the linear polymer has the function of a common dispersant, namely, increasing the wetting effect on the surface of the powder, making the particles more easily dispersed in the medium. In addition, during the heating process, the molecular chains of the linear polymer can form physical entanglements between the ceramic particles and between layers, making the connection between the layers more firm; and the thermal initiator will undergo thermal polymerization during the heating process, further improving the density of the green body; further, spherical powders of different particle sizes are used for stacking, and the appropriate particle size and proportion distribution can achieve a higher stacking density, which also makes it easier to achieve an increase in the density of the final product. BRIEF DESCRIPTION OF THE DRAWINGS
[0083] Figure 1 This is a SEM image of the first blank prepared in Application Example 1 of the present invention.
[0084] Figure 2 This is a SEM image of the first blank prepared in Application Example 4 of the present invention.
[0085] Figure 3 This is a SEM image of the zirconia ceramic product obtained in Application Example 1 of the present invention.
[0086] Figure 4 This is a SEM image of the zirconia ceramic product obtained in Application Example 4 of the present invention. DETAILED DESCRIPTION
[0087] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0088] It should be understood that, in the description of the present invention, the terms "first", "second", etc. are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first", "second", etc. may explicitly or implicitly include one or more of the features. In the description of the present invention, unless otherwise specified, "plurality" means two or more.
[0089] Modified zirconia ceramic powder A1
[0090] The preparation method of modified zirconia ceramic powder A1 comprises:
[0091] The initial zirconium oxide powder is yttria-doped zirconium oxide powder, wherein the yttria content is 5.8wt%, and the mass ratio of anhydrous ethanol:initial zirconium oxide powder:abrasive is 2:1:3, and 0.5wt% of a modifier (methacrylic acid) is added, wherein the mass ratio of the first grinding ball (diameter 10mm), the second grinding ball (diameter 7mm) and the third grinding ball (5mm) is 5:3:2. The initial zirconium oxide powder, the modifier and anhydrous ethanol are mixed, and the ball mill jar prepared with the mixed liquid is placed on a planetary ball mill at 700r / min for the first ball milling for 4h, and then placed in a blast drying oven for drying (temperature 70°C). The dried powder is ground with a mortar and passed through a 100-mesh sieve, and the part under the sieve obtains the modified zirconium oxide powder.
[0092] The initial zirconium oxide powder comprises:
[0093] The first particle size zirconium oxide has a particle size range of 800 to 1300 nm and is 70%;
[0094] 20% of the second particle size zirconium oxide with a particle size range of 200 to 500 nm;
[0095] The third particle size zirconium oxide with a particle size range of 50 to 150 nm contains 10%.
[0096] Modified zirconia ceramic powder A2
[0097] The preparation method of modified zirconia ceramic powder A2 comprises:
[0098] The initial zirconium oxide powder is yttria-doped zirconium oxide powder, wherein the yttria content is 5.8wt%, and the mass ratio of anhydrous ethanol:initial zirconium oxide powder:abrasive is 2:1:3, and 0.5wt% of a modifier (methacrylic acid) is added, wherein the mass ratio of the first grinding ball (diameter 10mm), the second grinding ball (diameter 7mm) and the third grinding ball (5mm) is 5:3:2. The initial zirconium oxide powder, the modifier and anhydrous ethanol are mixed, and the ball mill jar prepared with the mixed liquid is placed on a planetary ball mill at 700r / min for the first ball milling for 4h, and then placed in a blast drying oven for drying (temperature 70°C). The dried powder is ground with a mortar and passed through a 100-mesh sieve, and the part under the sieve obtains the modified zirconium oxide powder.
[0099] The initial zirconium oxide powder comprises:
[0100] The first particle size of zirconium oxide is 65% with a particle size range of 800 to 1300 nm;
[0101] The second particle size zirconium oxide with a particle size range of 200 to 500 nm is 25%;
[0102] The third particle size zirconium oxide with a particle size range of 50 to 150 nm contains 15%.
[0103] Modified zirconia ceramic powder A3
[0104] The preparation method of modified zirconia ceramic powder A3 comprises:
[0105] The initial zirconium oxide powder is yttria-doped zirconium oxide powder, wherein the yttria content is 5.8wt%, and the mass ratio of anhydrous ethanol:initial zirconium oxide powder:abrasive is 2:1:3, and 0.5wt% of a modifier (methacrylic acid) is added, wherein the mass ratio of the first grinding ball (diameter 10mm), the second grinding ball (diameter 7mm) and the third grinding ball (5mm) is 5:3:2. The initial zirconium oxide powder, the modifier and anhydrous ethanol are mixed, and the ball mill jar prepared with the mixed liquid is placed on a planetary ball mill at 700r / min for the first ball milling for 4h, and then placed in a blast drying oven for drying (temperature 70°C). The dried powder is ground with a mortar and passed through a 100-mesh sieve, and the part under the sieve obtains the modified zirconium oxide powder.
[0106] The initial zirconium oxide powder comprises:
[0107] The first particle size of zirconium oxide is 55% with a particle size range of 800 to 1300 nm;
[0108] 30% of the second particle size zirconium oxide with a particle size range of 200 to 500 nm;
[0109] The third particle size zirconium oxide with a particle size range of 50 to 150 nm contains 15%.
[0110] Modified zirconia ceramic powder D1
[0111] The preparation method of the modified zirconia ceramic powder D1 is the same as that of the modified zirconia ceramic powder A1, except that the first particle size zirconia with a particle size range of 800 to 1300 nm accounts for 100% of the initial zirconia powder and no zirconia powder with other particle sizes is contained.
[0112] Modified zirconia ceramic powder D2
[0113] The preparation method of modified zirconia ceramic powder D2 is the same as that of modified zirconia ceramic powder A1, except that the initial zirconia powder does not contain the third particle size zirconia with a particle size range of 50-150 nm, and the content of the second particle size zirconia with a particle size range of 200-500 nm is adjusted to 30%.
[0114] Modified zirconia ceramic powder D3
[0115] The preparation method of modified zirconia ceramic powder D3 is the same as that of modified zirconia ceramic powder A1, except that the initial zirconia powder does not contain the second particle size zirconia with a particle size range of 200-500nm, and the content of the third particle size zirconia with a particle size range of 50-150nm is adjusted to 30%.
[0116] Modified zirconia ceramic powder D4
[0117] The preparation method of the modified zirconia ceramic powder D4 is the same as that of the modified zirconia ceramic powder A1, except that the initial zirconia powder does not contain the first particle size zirconia with a particle size range of 800-1300 nm, and the content of the second particle size zirconia with a particle size range of 200-500 nm is adjusted to 55%, and the content of the third particle size zirconia is adjusted to 45%.
[0118] Modified zirconia ceramic powder D5
[0119] The preparation method of the modified zirconia ceramic powder D5 is the same as that of the modified zirconia ceramic powder A1, except that no modifier is added during the preparation process.
[0120] Example 1
[0121] This embodiment provides a zirconia ceramic slurry, which includes the following components in terms of mass percentage:
[0122]
[0123]
[0124] This embodiment also provides a method for preparing the zirconia ceramic slurry, which comprises the following steps:
[0125] A photosensitive resin (oligomer and active diluent), a photoinitiator and a linear polymer are first mixed in proportion, a dispersant and a defoamer are added, and an ultrasonic water bath is performed, and a mechanical stirring process is performed at the same time, wherein the water bath temperature is 60° C. and the water bath stirring time is 2 hours, to ensure that each component system in the photosensitive resin solution can be fully dissolved and dispersed, to obtain a first resin solution;
[0126] The second mixed zirconium oxide powder and the first resin liquid were mechanically stirred at 500 r / min for 1 hour, and then subjected to a second ball milling at a speed of 700 r / min, each ball milling for 1 hour, pausing for 10 minutes, and the second ball milling for a total of 15 hours to obtain a first slurry, and then a thermal initiator was added, and the third ball milling was continued at a speed of 700 r / min, each ball milling for 30 minutes, pausing for 5 minutes, and the third ball milling for a total of 1 hour to obtain a second slurry;
[0127] The second slurry is placed in a vacuum defoaming machine and defoamed for 3 hours under a vacuum degree of 0.1 MPa to obtain the zirconia ceramic slurry.
[0128] Example 2
[0129] This embodiment provides a zirconia ceramic slurry, which includes the following components in terms of mass percentage:
[0130]
[0131]
[0132] This embodiment also provides a method for preparing the zirconia ceramic slurry, which comprises the following steps:
[0133] A photosensitive resin (oligomer and active diluent), a photoinitiator and a linear polymer are first mixed in proportion, a dispersant and a defoamer are added, and an ultrasonic water bath is performed, and a mechanical stirring process is performed at the same time, wherein the water bath temperature is 60° C. and the water bath stirring time is 1.8 hours, to ensure that each component system in the photosensitive resin solution can be fully dissolved and dispersed, to obtain a first resin solution;
[0134] The second mixed zirconium oxide powder and the first resin liquid were mechanically stirred at 500 r / min for 2 h, and then subjected to a second ball milling at a speed of 700 r / min, each ball milling for 1.5 h, paused for 15 min, and the second ball milling for a total of 16 h to obtain a first slurry, and then a thermal initiator was added, and the third ball milling was continued at a speed of 600 r / min, each ball milling for 45 min, paused for 8 min, and the third ball milling for a total of 1.5 h to obtain a second slurry;
[0135] The second slurry is placed in a vacuum defoaming machine and defoamed for 4 hours under a vacuum degree of 0.1 MPa to obtain the zirconia ceramic slurry.
[0136] Example 3
[0137] This embodiment provides a zirconia ceramic slurry, which includes the following components in terms of mass percentage:
[0138]
[0139] This embodiment also provides a method for preparing the zirconia ceramic slurry, which comprises the following steps:
[0140] A photosensitive resin (oligomer and active diluent), a photoinitiator and a linear polymer are first mixed in proportion, a dispersant and a defoamer are added, and an ultrasonic water bath is performed, and a mechanical stirring process is performed at the same time, wherein the water bath temperature is 60° C. and the water bath stirring time is 1.5 hours, to ensure that each component system in the photosensitive resin solution can be fully dissolved and dispersed, to obtain a first resin solution;
[0141] The second mixed zirconium oxide powder and the first resin liquid were mechanically stirred at 400 r / min for 1.2 h, and then subjected to a second ball milling at a speed of 600 r / min, each ball milling for 0.5 h, paused for 5 min, and the second ball milling for a total of 16 h to obtain a first slurry, and then a thermal initiator was added, and the third ball milling was continued at a speed of 600 r / min, each ball milling for 15 min, paused for 2 min, and the third ball milling for a total of 1.0 h to obtain a second slurry;
[0142] The second slurry is placed in a vacuum defoaming machine and defoamed for 4 hours under a vacuum degree of 0.1 MPa to obtain the zirconia ceramic slurry.
[0143] Example 4
[0144] This embodiment provides a zirconia ceramic slurry. The zirconia ceramic slurry is the same as that of Embodiment 2 except that the modified zirconia powder D1 is used, and details thereof will not be repeated herein.
[0145] Example 5
[0146] This embodiment provides a zirconia ceramic slurry. The zirconia ceramic slurry is the same as that of Embodiment 3 except that the modified zirconia powder D1 is used, and details thereof will not be repeated here.
[0147] Example 6
[0148] This embodiment provides a zirconia ceramic slurry. The zirconia ceramic slurry is the same as that of Embodiment 1 except that the modified zirconia powder D2 is used, and details thereof will not be repeated here.
[0149] Example 7
[0150] This embodiment provides a zirconia ceramic slurry. The zirconia ceramic slurry is the same as that of Embodiment 1 except that the modified zirconia powder D3 is used, and details thereof will not be repeated here.
[0151] Example 8
[0152] This embodiment provides a zirconia ceramic slurry. The zirconia ceramic slurry is the same as that of Embodiment 1 except that the modified zirconia powder D4 is used, and details thereof will not be repeated here.
[0153] Example 9
[0154] This embodiment provides a zirconia ceramic slurry. The zirconia ceramic slurry is the same as that of Embodiment 1 except that the modified zirconia powder D5 is used, and details thereof will not be repeated here.
[0155] This embodiment uses unmodified zirconium oxide powder, which is hydrophilic and difficult to add to the resin-based system. It is difficult to add the full mass fraction of the powder during the slurry preparation process, and the viscosity is too high, so normal printing and performance testing cannot be performed.
[0156] Example 10
[0157] This embodiment provides a zirconia ceramic slurry. The zirconia ceramic slurry is the same as that of Embodiment 1 except that no dispersant is added, and thus will not be described in detail herein.
[0158] In this embodiment, no dispersant is added during the powder addition process. The dispersant mainly serves to reduce the viscosity of the slurry and to evenly disperse the powder in the resin-based system. Therefore, without the dispersant, it is impossible to add all the powders at the solid content, and the slurry viscosity is too high to perform subsequent normal printing and performance testing.
[0159] Embodiment 11
[0160] This embodiment provides a zirconia ceramic slurry. The zirconia ceramic slurry is the same as that of Embodiment 1 except that the dispersant is sodium dodecyl sulfate, and the details are not described again.
[0161] In Example 11, the dispersant is replaced by 12-alkyl sodium sulfate, which is not the preferred optimal dispersant of the present invention. Although it is also a surfactant for improving the powder dispersion effect, its dispersion effect and slurry stability are significantly inferior to BYK101 and BYK103 used in Examples 1 / 2 / 3. This will make the prepared slurry more viscous under the same conditions, which is not conducive to the printing molding process, and the density and final firing performance of the printed sample will be reduced.
[0162] Example 12
[0163] This embodiment provides a zirconia ceramic slurry, which is the same as that of Embodiment 1 except that the amount of the linear polymer is 4.5 wt % and the amount of the modified zirconia powder A1 added is adjusted accordingly, and will not be described again.
[0164] Example 13
[0165] This embodiment provides a zirconia ceramic slurry, which is the same as that of Embodiment 1 except that the amount of the linear polymer is 1.5 wt % and the amount of the modified zirconia powder A1 added is adjusted accordingly, and will not be described again.
[0166] Embodiment 14
[0167] This embodiment provides a zirconia ceramic slurry, which is the same as that of Embodiment 1 except that the amount of the thermal initiator is 0.02 wt % and the amount of the modified zirconia powder A1 added is adjusted accordingly, and will not be described again.
[0168] Embodiment 15
[0169] This embodiment provides a zirconia ceramic slurry, which is the same as that of Embodiment 1 except that the amount of the thermal initiator is 1 wt % and the amount of the modified zirconia powder A1 added is adjusted accordingly, and will not be described again.
[0170] Example 16
[0171] This embodiment provides a zirconia ceramic slurry, which is the same as that of Embodiment 1 except that the amount of the thermal initiator is 1.5 wt % and the amount of the modified zirconia powder A1 added is adjusted accordingly, and will not be described again.
[0172] Comparative Example 1
[0173] This comparative example provides a zirconia ceramic slurry, which is the same as Example 1 except that no thermal initiator is added and the amount of modified zirconia powder A1 added is adjusted accordingly, and no further details are given here.
[0174] Comparative Example 2
[0175] This comparative example provides a zirconia ceramic slurry, which is the same as Example 1 except that no linear polymer is added and the amount of modified zirconia powder A1 added is adjusted accordingly, and no further details are given here.
[0176] Application Example 1
[0177] This application example provides a zirconia ceramic product, and the preparation method of the zirconia ceramic product includes:
[0178] (1) Light-curing 3D printing: at a light intensity of 40 mW / cm 2 , under a surface light source of visible light with a wavelength of 450 nm, the zirconia ceramic slurry obtained in Example 1 was 3D printed with a layer thickness of 25 μm and then exposed and cured for 8 seconds to obtain a first green blank;
[0179] (2) Sample disassembly and cleaning: Remove the first blank from the printing platform and use cleaning fluid or alcohol to remove the support and clean it. To prevent the residual cleaning fluid from corroding the sample, blow away the residual cleaning fluid with a spray gun after cleaning.
[0180] (3) Sample drying: Use a low-temperature resistance furnace for programmed thermal curing: starting from room temperature, heat up to 75°C at a rate of 0.2°C / min and keep warm for 60 min; heat up to 85°C at a rate of 0.1°C / min and keep warm for 60 min; heat up to 95°C at a rate of 0.2°C / min and keep warm for 100 min; heat up to 100°C at a rate of 0.1°C / min and keep warm for 120 min; heat up to 105°C at a rate of 0.1°C / min and keep warm for 60 min; heat up to 110°C at a rate of 0.2°C / min and keep warm for 60 min; heat up to 115°C at a rate of 0.1°C / min and keep warm for 90 min; heat up to 130°C at a rate of 0.15°C / min and keep warm for 120 min; then cool to room temperature in the furnace to obtain a dried second blank;
[0181] (4) Debinding and sintering: The second green billet was placed in a debinding furnace for debinding (segmented debinding): starting from room temperature, the temperature was increased to 170°C at a rate of 0.8°C / min and then kept at this temperature for 120 min; the temperature was increased to 325°C at a rate of 1°C / min and then kept at this temperature for 180 min; the temperature was increased to 430°C at a rate of 1°C / min and then kept at this temperature for 180 min; the temperature was increased to 500°C at a rate of 1.2°C / min and then kept at this temperature for 120 min; the temperature was decreased to 300°C at a rate of 2°C / min and then cooled to room temperature with the furnace to obtain a degreased sample.
[0182] Sintering: The degreased sample was heated from room temperature to 900°C at a rate of 4°C / min and kept warm for 60 minutes, then heated to 1530°C at a rate of 3°C / min and kept warm for 120 minutes, then cooled to 800°C at a rate of 10°C / min and cooled to room temperature with the furnace to obtain a zirconia ceramic product.
[0183] Application Example 2
[0184] This application example provides a zirconia ceramic product, and the preparation method of the zirconia ceramic product includes:
[0185] (1) Light-curing 3D printing: at a light intensity of 45 mW / cm 2 , under a surface light source of visible light with a wavelength of 450 nm, the zirconia ceramic slurry obtained in Example 2 was 3D printed with a layer thickness of 25 μm and then exposed and cured for 10 seconds to obtain a first green blank;
[0186] (2) Sample disassembly and cleaning: Remove the first blank from the printing platform and use cleaning fluid or alcohol to remove the support and clean it. To prevent the residual cleaning fluid from corroding the sample, blow away the residual cleaning fluid with a spray gun after cleaning.
[0187] (3) Drying: Use a low-temperature resistance furnace for programmed thermal curing: starting from room temperature, heat up to 75°C at a rate of 0.2°C / min and keep warm for 60 min, heat up to 85°C at a rate of 0.15°C / min and keep warm for 60 min, heat up to 95°C at a rate of 0.17°C / min and keep warm for 100 min, heat up to 100°C at a rate of 0.18°C / min and keep warm for 120 min, heat up to 105°C at a rate of 0.1°C / min and keep warm for 60 min, heat up to 110°C at a rate of 0.16°C / min and keep warm for 60 min, heat up to 115°C at a rate of 0.1°C / min and keep warm for 90 min, heat up to 200°C at a rate of 0.2°C / min and keep warm for 120 min, then cool to room temperature with the furnace to obtain a dried second blank;
[0188] (4) Debinding and sintering: The second green billet was placed in a debinding furnace for debinding (segmented debinding): starting from room temperature, the temperature was increased to 170°C at a rate of 0.8°C / min and then kept at this temperature for 120 min; the temperature was increased to 325°C at a rate of 1°C / min and then kept at this temperature for 180 min; the temperature was increased to 430°C at a rate of 1°C / min and then kept at this temperature for 180 min; the temperature was increased to 500°C at a rate of 1.2°C / min and then kept at this temperature for 120 min; the temperature was decreased to 300°C at a rate of 2°C / min and then cooled to room temperature with the furnace to obtain a degreased sample.
[0189] Sintering: The degreased sample was heated from room temperature to 900°C at a rate of 4°C / min and kept warm for 60 minutes, then heated to 1530°C at a rate of 3°C / min and kept warm for 120 minutes, then cooled to 800°C at a rate of 10°C / min and cooled to room temperature with the furnace to obtain a zirconia ceramic product.
[0190] Application Example 3
[0191] This application example provides a zirconia ceramic product, and the preparation method of the zirconia ceramic product includes:
[0192] (1) Light-curing 3D printing: at a light intensity of 50 mW / cm 2 , under a surface light source of visible light with a wavelength of 450 nm, the zirconia ceramic slurry obtained in Example 3 was 3D printed with a layer thickness of 25 μm and then exposed and cured for 12 seconds to obtain a first green blank;
[0193] (2) Sample disassembly and cleaning: Remove the first blank from the printing platform and use cleaning fluid or alcohol to remove the support and clean it. To prevent the residual cleaning fluid from corroding the sample, blow away the residual cleaning fluid with a spray gun after cleaning.
[0194] (3) Drying: Use a low-temperature resistance furnace for programmed thermal curing: starting from room temperature, heat up to 75°C at a rate of 0.2°C / min and keep warm for 60 min, heat up to 85°C at a rate of 0.2°C / min and keep warm for 60 min, heat up to 95°C at a rate of 0.15°C / min and keep warm for 100 min, heat up to 100°C at a rate of 0.1°C / min and keep warm for 120 min, heat up to 105°C at a rate of 0.2°C / min and keep warm for 60 min, heat up to 110°C at a rate of 0.1°C / min and keep warm for 60 min, heat up to 115°C at a rate of 0.2°C / min and keep warm for 90 min, heat up to 150°C at a rate of 0.2°C / min and keep warm for 120 min, then cool to room temperature with the furnace to obtain a dried second blank;
[0195] (4) Debinding and sintering: The second green billet was placed in a debinding furnace for debinding (segmented debinding): starting from room temperature, the temperature was increased to 170°C at a rate of 0.8°C / min and then kept at this temperature for 120 min; the temperature was increased to 325°C at a rate of 1°C / min and then kept at this temperature for 180 min; the temperature was increased to 430°C at a rate of 1°C / min and then kept at this temperature for 180 min; the temperature was increased to 500°C at a rate of 1.2°C / min and then kept at this temperature for 120 min; the temperature was decreased to 300°C at a rate of 2°C / min and then cooled to room temperature with the furnace to obtain a degreased sample.
[0196] Sintering: The degreased sample was heated from room temperature to 900°C at a rate of 4°C / min and kept warm for 60 minutes, then heated to 1530°C at a rate of 3°C / min and kept warm for 120 minutes, then cooled to 800°C at a rate of 10°C / min and cooled to room temperature with the furnace to obtain a zirconia ceramic product.
[0197] Application Examples 4 to 16 and Comparative Application Examples 1 to 2
[0198] Application Examples 4 to 16 and Application Comparative Examples 1 to 2 provide a zirconia ceramic product. Except for using the zirconia ceramic slurry in Examples 4 to 16 and Comparative Examples 1 to 2, the rest of the zirconia ceramic product is the same as Application Example 1, which will not be repeated here.
[0199] The SEM images of the first blanks printed in Application Example 1 and Application Example 4 are as follows: Figure 1 and Figure 2 As shown, from Figure 1 and Figure 2 It can be seen that the particle distribution of the green blank in Application Example 1 is more uniform and the density is higher. The SEM images of the zirconia ceramic products obtained in Application Example 1 and Application Example 4 are as follows: Figure 3 and Figure 4 As shown, from Figure 3It can be seen that the grains inside the ceramic body of Application Example 1 grow denser, the morphology is more regular and spherical, and the size distribution is relatively uniform; this indicates that through the particle size grading of the powder, the regulation of the additives in the slurry, combined with the drying treatment, the densified growth of the ceramic body can be achieved, and higher mechanical properties of the ceramic body can be achieved.
[0200] Test method: The solid content of zirconia ceramic slurry is tested by ignition reduction method (weigh a certain amount of slurry m, heat to 650℃ for 4h to ensure that the organic components are completely volatilized, weigh the mass of the residual substance m1, slurry solid content = m1 / m*100%), and the solid content of zirconia ceramic slurry is tested by digital viscometer (ISO 19613:2018) at 20℃ for 30S -1 The viscosity under shear rate, the density of the first green body, the second green body and the zirconia ceramic product was tested by a density balance (GB / T 25995-2010), and the flexural strength of the zirconia ceramic product was tested by a three-point bending strength test method (GB 30367-2013).
[0201] The test results of the above application examples and application comparison examples are shown in Table 1.
[0202] Table 1
[0203]
[0204] From Table 1, we can see the following points:
[0205] (1) Comprehensive application examples 1 to 3 show that the zirconia ceramic slurry provided by the present invention has the advantages of high solid content and uniform distribution. After 3D printing, the uniformity and density of the green blank can be improved, and the density of the second green blank is further improved after drying. The density of the final zirconia ceramic product is 6.015 g / cm 3 Above, and the flexural strength of the final zirconia ceramic product is above 785MPa;
[0206] (2) It can be seen from the combined application examples 1 and 6 to 8 that the zirconium oxide powder with a specific grading in application example 1 is compared with the zirconium oxide powder with no grading or grading distribution not within the preferred range, or even unreasonable grading in application examples 6 to 8. The solid content and viscosity of the slurry in application example 1 are within the excellent printable range, and the flexural strength of the final zirconia ceramic product reaches 785 MPa. However, in application examples 6 to 8, due to the unreasonable grading mentioned above, the slurry viscosity is too high, or the first green body density is low, and the final product density and flexural strength are both reduced. Compared with application examples 4 and 5, application examples 2 and 3 are the same as above, because no grading is performed, resulting in a decrease in the density of the first green body after solidification, and the final product density and flexural strength are both reduced. It can be seen that the solid content of the slurry is the main factor affecting the slurry viscosity and the density of the solidified green body, that is, the density of the first green body, among which the powder grading is the key influencing factor. The present invention can obtain a zirconia ceramic product with higher flexural strength by reasonably grading the zirconium oxide powder.
[0207] (3) It can be seen from the combined application examples 1 and 11 that the preferred dispersant used in application example 1 has a better dispersing effect, and the dispersing effect and slurry stability of the sodium dodecyl sulfate used in application example 11 are lower than those in application example 1, which will make the prepared slurry viscosity greater under the same conditions, which is not conducive to the printing molding process, and the density and final firing performance of the printed sample will be reduced. This shows that the present invention has a better printing effect by selecting a suitable type of dispersant, and the final zirconia ceramic product has a higher flexural strength;
[0208] (4) In Application Example 12, the amount of linear polymer is increased, and the content of powder is correspondingly reduced. The solid content is reduced to 79%, the organic components are increased, and the viscosity of the slurry is reduced, but the solidification density of the blank is reduced. The linear polymer is within the range designed by the present invention, which is a verified optimal range. If the content of the linear polymer is increased beyond the range, the density of the blank is not significantly increased during the drying and heat treatment process, because the appropriate amount of content can achieve the effect of increasing the density of the blank. Therefore, since the density of the printing and curing itself is smaller than that of Application Example 1, the density and strength of the final fired state are also lower than those of Application Example 1. Application Example 13 reduces the content of the linear polymer to a range below the lower limit. On the one hand, the solid content of the powder in the slurry is increased, so that the viscosity of the slurry is significantly increased, and the solidification density of the blank is improved. However, because the linear polymer that plays a role in improving the interlayer bonding during the drying and heat curing is too small, the density is not significantly increased during the drying and heat treatment process, so the final fired density and mechanical properties are lower than those of Application Example 1. This shows that the present invention preferably controls the content of the linear polymer within a reasonable range, which has better flexural strength.
[0209] (5) In Application Example 14, the content of thermal initiator is reduced to below the lower limit of the preferred range of the present invention, the solid content of the slurry is slightly increased to 80.28%, the viscosity of the slurry preparation process is slightly increased, and the density of the first green body after printing is almost the same. However, in the drying heat treatment process, the thermal initiator that mainly increases the thermal curing density is less, so the density increase of the green body during the drying process is reduced, and the corresponding final firing density and mechanical properties are lower than those in Application Example 1. The amount of thermal initiator added in Application Example 15 is 1wt%, and the amount of thermal initiator added in Application Example 16 is 1.5wt%. The flexural strengths of the zirconia ceramic products in Application Example 15 and Application Example 1 are 730MPa and 785MPa, respectively, which have better performance than Application Example 16. Furthermore, the amount of thermal initiator in Application Example 1 is within the preferred range of 0.1-0.3%. Compared with Application Example 15, the flexural strength of the zirconia ceramic product is significantly improved. This shows that Application Examples 15-16 are configured better than Application Example 1. The viscosity of the slurry is slightly decreased, but the density of the first green body after curing is also reduced due to the decrease in solid content. Although the density of the second green body after drying is higher than that of the first green body, the degree of improvement is equivalent to that in Example 1, that is, the preferred 0.1-0.3wt% thermal initiator of the present invention can meet the corresponding density increase, and the additional addition actually reduces the solid content of the powder in the slurry. Application Example 16 has a significant decrease in solid content, which has a counterproductive effect on the density increase of the green body. The final fired density and mechanical properties of the corresponding ceramic product are lower than those in Example 1.
[0210] (6) In the comparative example 1, no thermal initiator was added, resulting in a low density of the second green body after drying, and the flexural strength of the zirconia ceramic product after final firing was significantly reduced to 720 MPa. In the comparative example 2, no linear polymer was added, resulting in an even lower density of the dried second green body and a high viscosity of the slurry, and the flexural strength of the zirconia ceramic product after final firing was significantly reduced to 755 MPa. This shows that the present invention has a synergistic effect with the modified zirconia powder by adding a linear polymer and a thermal initiator to the slurry, and can synergistically improve the flexural strength of the zirconia ceramic product.
[0211] The invention uses the above embodiments to illustrate the detailed features of the present invention, but the present invention is not limited to the above detailed features, that is, it does not mean that the present invention must rely on the above detailed features to be implemented. Those skilled in the art should understand that any improvement to the present invention, equivalent replacement of the technical features selected by the present invention, addition of auxiliary technical features, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A zirconia ceramic slurry, characterized in that: The zirconia ceramic slurry comprises: zirconia powder and a resin component; The resin component includes a photosensitive resin, a photoinitiator, a linear polymer and a thermal initiator.
2. The zirconia ceramic slurry according to claim 1, characterized in that: The zirconium oxide powder is modified zirconium oxide powder; Preferably, the modified zirconium oxide powder is yttria-doped zirconium oxide powder modified by a modifier; Preferably, the content of yttrium oxide in the yttrium oxide-doped zirconium oxide powder is 5wt% to 6.5wt%; Preferably, the amount of the modifier added is 0.4-1wt% of the mass fraction of the modified zirconium oxide powder; Preferably, the modifier includes any one of methacrylic acid, 3-(methacryloyloxy)propyltrimethoxysilane or stearic acid, or a combination of at least two thereof.
3. The zirconia ceramic slurry according to claim 2, characterized in that: The preparation of the modified zirconium oxide powder comprises: The initial zirconium oxide powder, the modifier and the organic solvent are mixed, and the first ball milling is performed, and then the modified zirconium oxide powder is obtained by drying and sieving in sequence; Preferably, the organic solvent comprises ethanol; Preferably, in the first ball milling, the organic solvent: initial zirconium oxide powder: abrasive = 1-3: 1: 2-5 in terms of mass ratio; Preferably, the sieving is through a 100 mesh sieve; Preferably, the rotation speed of the first ball mill is 500-1000 r / min; Preferably, the first ball milling time is 4 to 6 hours; Preferably, the initial zirconia powder comprises zirconia of a first particle size, zirconia of a second particle size and zirconia of a third particle size, wherein the particle size of the zirconia of the first particle size is larger than the particle size of the zirconia of the second particle size, and the particle size of the zirconia of the second particle size is larger than the particle size of the zirconia of the third particle size; The particle size of the first particle size zirconium oxide ranges from 800 to 1300 nm; Preferably, the particle size of the second particle size zirconium oxide is in the range of 200 to 500 nm; Preferably, the particle size of the third particle size zirconium oxide is in the range of 50 to 150 nm; Preferably, the mass fraction of the first particle size zirconium oxide in the whole zirconium oxide powder is 50-70%; Preferably, the mass fraction of the second particle size zirconium oxide in the whole zirconium oxide powder is 15-40%; Preferably, the mass fraction of the third particle size zirconium oxide in the whole zirconium oxide powder is 0.1-15%.
4. The zirconia ceramic slurry according to any one of claims 1 to 3, characterized in that: The zirconia ceramic slurry comprises: 80-83wt% of zirconia powder and 17-20wt% of a resin component; Preferably, the content of the photosensitive resin is 6 to 14.8 wt % based on the zirconia ceramic slurry; Preferably, the content of the photoinitiator is 2-4 wt % based on the zirconia ceramic slurry; Preferably, the content of the thermal initiator is 0.1 to 1 wt%, preferably 0.1 to 0.3 wt%, based on the zirconia ceramic slurry; Preferably, the content of the linear polymer is 2 to 4 wt% based on the zirconia ceramic slurry; Preferably, the photosensitive resin comprises, by weight percentage: 2 to 5 wt % oligomer and 4 to 9.8 wt % reactive diluent; Preferably, the oligomer comprises an acrylate oligomer, preferably any one or a combination of at least two of epoxy acrylate, polyester acrylate or polyurethane acrylate; Preferably, the reactive diluent comprises any one or a combination of at least two of hydroxyethyl methacrylate, isooctyl acrylate, cyclic trimethylolpropane formal acrylate, 1,6-hexanediol diacrylate, triethylene glycol diacrylate, pentaerythritol triacrylate, tetrahydrofuran methyl acrylate, ditrimethylolpropane tetraacrylate or polyethylene glycol diacrylate; Preferably, the photoinitiator comprises any one of 1-hydroxycyclohexyl phenyl ketone, bis-2,6-difluoro-3-pyrrolophenyl titanocene, phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, 2-hydroxy-2-methyl-1-phenyl-1-propanone, diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide, photoinitiator 1300 or camphorquinone, or a combination of at least two thereof; Preferably, the thermal initiator comprises an organic peroxide initiator, preferably any one of dicumyl peroxide, dibenzoyl peroxide or tert-butyl hydroperoxide or a combination of at least two thereof; Preferably, the linear polymer comprises any one of polycaprolactone, polyethylene glycol or polyisoboric acid ester, or a combination of at least two thereof.
5. The zirconia ceramic slurry according to any one of claims 1 to 4, characterized in that: The zirconia ceramic slurry also includes additives; Preferably, the additives include 1-2% dispersant and 0.1-0.3% defoamer in terms of mass percentage; Preferably, the dispersant includes any one of stearic acid, oleic acid, polyvinyl pyridone, sodium polyacrylate, polypropoxy quaternary ternary ammonium chloride, ammonium polyacrylate, silane coupling agent, BYK101, BYK103, KOS110, KOS163, Solsperse 2000, Digo 685, Shanggao 9030 or Shanggao 9070, or a combination of at least two thereof; Preferably, the silane coupling agent includes any one of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane or γ-methacryloxypropyltrimethoxysilane or a combination of at least two thereof; Preferably, the defoaming agent includes any one of n-octanol, BYK-1790, BYK-1794, Airex 920, AKN-39203 or AKN-3386, or a combination of at least two thereof.
6. A method for preparing the zirconia ceramic slurry according to any one of claims 1 to 5, characterized in that: The preparation method comprises: first mixing a photosensitive resin, a photoinitiator and a linear polymer to obtain a first resin solution; The second mixed zirconium oxide powder and the first resin liquid are stirred and second ball-milled in sequence to obtain a first slurry, and a thermal initiator is added and a third ball-milling is performed to obtain a second slurry; The second slurry is defoamed to obtain the zirconia ceramic slurry.
7. The preparation method according to claim 6, characterized in that: Additives are also added during the first mixing; Preferably, the temperature of the first mixing is 50-70°C; Preferably, the first mixing time is 1 to 2 hours; Preferably, the stirring time is 1 to 2 hours; Preferably, the stirring speed is 800-1400 r / min; Preferably, the rotation speed of the second ball mill is 600-900 r / min; Preferably, the second ball milling is performed for 0.5 to 1.5 hours, and then paused for 5 to 15 minutes; Preferably, the second ball milling time is 8 to 16 hours; Preferably, the rotation speed of the third ball mill is 600-900 r / min; Preferably, the third ball milling time is 1 to 2 hours; Preferably, the third ball milling is performed for 15 to 45 minutes, followed by a pause of 2 to 8 minutes; Preferably, the vacuum degree of the defoaming treatment is -0.05 to -0.1 MPa; Preferably, the defoaming time of the defoaming treatment is 2 to 4 hours.
8. A method for producing a zirconia ceramic product, characterized in that: The production method comprises: The zirconia ceramic slurry according to any one of claims 1 to 5 is subjected to 3D printing to obtain a first green blank; The first green body is dried, degreased and sintered in sequence to obtain the zirconia ceramic product.
9. The production method according to claim 8, characterized in that: The drying temperature is 120-200°C; Preferably, the drying insulation time is 2 to 4 hours.
10. A zirconia ceramic product, characterized in that: The zirconia ceramic product is produced by the production method of the zirconia ceramic product according to claim 8 or 9; Preferably, the green body density of the zirconia ceramic product is ≥3.6 g / cm 3 .
Citation Information
Patent Citations
Ceramic slurry for continuous 3D printing and preparation method and printing method thereof
CN115368123A
High-solid-phase zirconia ceramic slurry as well as preparation method and application thereof
CN116655374A
Water-based photo-thermal double-effect cured ceramic slurry as well as preparation method and application thereof
CN116947503A
Zirconia ceramic slurry, preparation method and application thereof, 3D printing zirconia ceramic and application thereof
CN118145989A
Cited By
Ceramic slurry for zirconia ceramic bonding and preparation method and application thereof
CN122167185A